The relationship between employer branding and talent management: a study on manufacturing sector - Selva Raja, Hemananthiny; Aris, Amir; Mohamad, Norhidayah (Ascociacion Internacional de Economia Aplicada, 2021)
Talent management is a common attraction and retention technique for talented workers in the current business scenario. Still, talent management contributes to the more significant appeal, and retention of employees is an unexplored area in the manufacturing industry. In Malaysia, employer branding is gaining significance. While the idea of the Employer brand has become a routine for companies, several researchers have recently attracted the attention of this field. Developing, recruiting, and keeping workers is a great challenge for every company. The purpose of this study is to explore the relationship between positions in employer branding and talent management. The paper aims to analyze the current state of the manufacturing industry in branding roles and assess their effect on talent management. The research seeks to address the employer branding and talent acquisition concept and the company's techniques. As a result, this study aims to look into the functions of employer branding in fostering employee talent management. For a better understanding of the relationship, this research proposes a conceptual model. This research is then evolved into a concrete study hypothesis for future investigations. The goal is that the researcher's findings will reveal a substantial link between employer branding positions and talent management. For relevant practitioners and new researchers, this study will be a possible eye-opener.